2006
DOI: 10.1183/09031936.06.00075905
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine induces contractile and relaxant effects in canine nasal venous systems

Abstract: Acetylcholine (ACh) induces nasal congestion at low doses but decongestion at high doses. The current study investigated the vascular mechanisms underlying this biphasic nasal airway response in dogs.Collecting and outflow veins from anterior and posterior nasal venous systems and the septal mucosa (containing sinusoidal venous plexuses) were isolated. The in vitro isometric tension of the vascular segments was monitored to reflect vascular reactivity. Immunohistochemical localisation of reduced nicotinamide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In vitro findings show that ACh at low concentrations relaxes posterior collecting veins (PCV) but constricts other veins while, at higher concentrations, ACh constricts all veins. 7 The results support the hypothesis that the nasal congestion that underlies nasal obstruction is caused by dilatation of intranasal PCVs coupled with constriction of extranasal outflow veins. It is now known that ACh can elicit vasodilatation or vasoconstriction via activation of different muscarinic receptor subtypes.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…In vitro findings show that ACh at low concentrations relaxes posterior collecting veins (PCV) but constricts other veins while, at higher concentrations, ACh constricts all veins. 7 The results support the hypothesis that the nasal congestion that underlies nasal obstruction is caused by dilatation of intranasal PCVs coupled with constriction of extranasal outflow veins. It is now known that ACh can elicit vasodilatation or vasoconstriction via activation of different muscarinic receptor subtypes.…”
supporting
confidence: 80%
“…The ACh-induced vasodilatation in the nose is nitric oxide dependent, whereas the induced contraction is nitric oxide independent. 7 Results of immunohistochemical studies showed the presence of all five known muscarinic receptor subtypes in the nasal veins, with predominance of M 1 and M 3 in the endothelium of collecting veins and in the smooth muscles of outflow veins. This is in agreement with the findings from the functional experiments in which both M 1 and M 3 are involved in mediating the ACh-induced relaxation in collecting veins or contraction in the outflow veins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetylcholine acts on peripheral muscarinic receptors present on epithelium, submucosal glands, arterial, and capacitance vessels 30 and exerted different actions on components of the nasal vascular bed. 31,32 However, the principal function of the parasympathetic cholinergic nerves is to control nasal mucus secretion 2,33 and not vascular reactivity.…”
Section: Discussionmentioning
confidence: 99%